John Marshall and the Heroic Age of the Supreme Court - Newmyer, R. Kent (Book collections on Project MUSE., 2001)
John Marshall (1755-1835) was arguably the most important judicial figure in American history. As the fourth chief justice of the United States Supreme Court, serving from 1801 to1835, he helped move the Court from the fringes of power to the epicenter of constitutional government. His great opinions in cases like Marbury v. Madison and McCulloch v. Maryland are still part of the working discourse of constitutional law in America. Drawing on a new and definitive edition of Marshall's papers, R. Kent Newmyer combines engaging narrative with new historiographical insights in a fresh interpretati.